Determinant Factors in the Implementation of Merit System: An Overview of Indonesian Case - Malik, Kurniawan Jabar; Prasojo, Eko (Asian Journal of Social and Humanities, 2023)
It is believed that implementing and realizing a merit system in managing government resources not only increases professionalism but also anticipates the occurrence of corruption. A comprehensive merit system can also encourage further positive impacts, especially on the investment climate and boosting the national economy. The enactment of the Civil Service Law is the government's step in realizing a merit system in Indonesia. However, approaching a decade of implementation, admitting the merit system still leaves some outwork and shortcomings. The strong culture of primordialism, patronage, and nepotism affects human resource management at various levels of the Indonesian government. Meanwhile, Indonesia has a noble ambition to implement a comprehensive merit system in the upcoming golden Indonesia period of 2045. This begins by determining the achievements of the merit system to produce professional ASN as a foundation by 2029. This study will further discuss what merit system principles as factors can be determined and implemented for Indonesian government institutions. Considering merit system principles such as strengthening capacity and capability, openness and impartiality, empowerment, and effective leadership is believed to encourage widespread and comprehensive implementation of the merit system. The elements of an optimal and effective merit system in the workplace will form professional employees, foster better societal conditions, and ultimately have a broader positive impact at the regional and national levels.